Experience of girls on menstrual hygiene and health - Uprety, Durga (Geographical Journal of Nepal, 2024)
This study explores and analyses the lived experiences and challenges faced by girl in menstrual hygiene and health during their menstruation in school. While exploring the experiences the study related to liberal feminism prospect as girls' personal experiences in menstrual hygiene and health followed the empowerment theory of three key dimensions i.e. agency, resources, and achievements, and applied phenomenological study designed. Information was collected and analyzed by transcribing the record in the native language, coding, creating themes, and interrelationships of themes. Interpretative Phenomenological Analysis (IPA). Results show that girls were able to empower, foster confidence, and change individuals and society through schools and retain them in the school education system. Better service and an enabling environment from colleagues, teachers, and family are important. This is drawn from the study that, peer education and boys’ involvement in menstrual hygiene and health issues in school education and service improvement as well as health promotion are recommended to be treated as a priority in the future.